Geospatial Assessment of Freshwater Quality for Heavy Metals and its Potential Health Risks Using Geoinformatics and Water Index Models in Gilgit-Baltistan-Pakistan - Naila Jabeen; Lubna Ghazal; Humaira Kanwal; Tayyab Raza Fraz; Muhammad Farrakh Nawaz; Liaquat Karim; Faten Khalid Karim; Samih M. Mostafa; Altaf Hussain Lahori (International Journal of Environmental Research, 2026)
Access to safe drinking water is a growing global challenge, with billions of people exposed to water scarcity and contamination risks. Heavy metals in drinking water are of particular concern due to their toxic effects on human health and ecosystems. This study assessed the drinking water quality of Hunza Valley, Gilgit-Baltistan, Pakistan, where no comprehensive geospatial evaluation had previously been conducted. A total of 66 water samples from springs and glaciers were analyzed for physico-chemical parameters and heavy metals (Fe, Ni, Cd, Cr-VI, As, and Pb). Statistical analysis (correlation, principal component analysis and cluster analysis), water quality indices (Water Quality Index and Synthetic Pollution Index), human health risk assessment (Hazard Quotient and Hazard Index) and geostatistical interpolation (Ordinary Kriging) were employed. Results showed that As (77%), Pb (34%), Cd (25%), and Cr-VI (9%) exceeded WHO limits, while Fe and Ni remained within permissible levels. WQI classified 59% of samples as unfit for human consumption, while SPI designated 26% as unsafe. PCA extracted four significant factors explaining 67% of total variance, and hotspot mapping highlighted Aliabad, Dorkhun, and Ganish as most contaminated villages. The hazard quotient and hazard index for non-carcinogenic health risk showed very few samples with significant health risk. The geospatial maps of health risk showed higher geospatial variability for arsenic, lead and iron whereas low variations were observed for cadmium, chromium and nickel. The TCRI values revealed As, Cd, Cr, Pb and Ni pose significant carcinogenic health risk with geospatial variation highlighting the western side of the district. The findings emphasize the urgent need for feasibility studies for treatment facilities, regular monitoring, cancer specific health risk studies to protect public health in Hunza Valley. This research provides a framework for sustainable water management aligned with SDG-6.